Teacher’s Experience in Presenting Vocabulary to Young EFL Learners - Yetti Fajriati (English Education and Applied Linguistics Journal (EEAL Journal), 2020)
This research aims to find out the techniques in presenting vocabulary to young EFL learners and to investigate difficulties and constraints as perceived by teachers in teaching vocabulary to young learners. A qualitative case study design will be used in this research. Data will be taken from teaching and learning activities by using observation and interview. The collected data will be classified, analyzed and concluded. This research is expected to be used as a reference for potential young learners’ teachers to teach in the future.